Anti-MRSA activity of abietane diterpenes from Coleus blumei Benth - Jurkaninová, Sabína; Kubínová, Renata; Nejezchlebová, Marcela; Gazdová, Markéta; Hanáková, Zuzana; Dall'Acqua, Stefano (Natural product research, 2021)
Two heretofore uncharacterised abietane diterpenes, sincoetsin C (1) and 3-hydroxyspirocoleon 7-O-β-D-glucoside (4), were isolated from a methanolic extract of Coleus blumei Benth. (Lamiaceae), along with the known compounds, scutellarioidone A (2) and spirocoleon 7-O-β-D-glucoside (3) using chromatographic techniques. Their structures were determined by 1D and 2D nuclear magnetic resonance including HSQC, HMBC, COSY and NOESY experiments, mass spectrometry (HR-MS) and other spectroscopic methods (UV, IR). Their antibacterial activity against the reference strain of methicillin-resistant Staphylococcus aureus subsp. aureus CCM 4750 (MRSA) was evaluated using optical absorption to obtain quantitative information on their growth. All isolated compounds displayed anti-MRSA 4750 activity at the concentration of 512 μg/mL. Sincoetsin C (1) was the abietane diterpene most active against MRSA 4750, with a minimum inhibitory concentration of 128 μg/mL.
Keywords: Abietanes; diterpeny abietanové; Diterpenes; Methicillin-Resistant Staphylococcus aureus; diterpeny; Phytochemicals; Staphylococcus; Coleus; fytonutrienty; methicilin rezistentní Staphylococcus aureus